Efeito agudo da Kinesio Taping® sobre a força isométrica máxima de preensão manual e resistência de força em esportistas saudáveis - Zanchet, Marcos Atrib (2012)
Given the increased use of tape Kinesio Taping ( KT ) by professionals working in sports and rehabilitation , it is necessary to conduct studies that focus on the effects of this method . As there are several proposed benefits from the application of KT , the objective is to quantify the physical effects of cutaneous stimulation with Kinesio Taping in the levels of maximal isometric strength and handgrip strength endurance . The present study is an experimental , repeated measures . Will be invited to compose the sportsmen young males , which do not have allergy to the material of the bandage or injury in the upper limbs . For collection of levels of muscular strength and endurance will use digital handgrip dynamometer . Data analysis will be performed with the Statistical Package for the Social Sciences. A descriptive presentation of the data will average and standard deviation . A simple analysis of variance ANOVA and post hoc Bonferroni test will be used to compare the difference between different groups banding